Book reviews: “Shahriar Shahriari, An Invitation to Combinatorics”, Cambridge Mathematical Text- books, xv + 613 p. 2022. ISBN 978-1-108-47654-6/hbk; 978-1-108-56870-8/ebook. - MALA, Firdous Ahmad (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
Combinatorics is a branch of mathematics that deals with counting problems and some other related concepts. Knowledge of the basic principles of combinatorics could greatly simplify the task of counting. The present book attempts at an accessible, amicable and conversational exposition of the art and the science of counting.